Rocky reef biodiversity survey: Punta Pardelas, Argentina - Bravo, Gonzalo (2021)
Temperate rocky reefs in the SW Atlantic are productive areas that support highly diverse communities of invertebrates, algae and fishes. Rocky outcrops form complex structures which offer a diversity of microhabitats that lead to a great variety of co-existing species. Subtidal biodiversity within the Natural Protected Area Península Valdés is largely unexplored and studies are mainly limited to fish. A total of 560 high definition photoquadrats from seven rocky reefs (1-25 m depth) at Punta Pardelas were obtained during March 2019. In total, 4491 occurrences were recorded and identified to phyla (n = 2), superclasses (n = 1), classes (n = 5), subclasses (n = 2), orders (n = 2), families (n = 1), subfamilies (n = 1), genera (n = 10) and species (n = 43) levels. This dataset was developed to provide a baseline inventory of Punta Pardelas inside the Natural Protected Area, that was only partially reported more than 50 years ago. Such data represent the first step towards monitoring these less-accessible ecosystems.